Ergodic site amplification model for central and eastern North America. Issue 1 (February 2020) - Stewart, Jonathan P.; Parker, Grace A.; Atkinson, Gail M.; Boore, David M.; Hashash, Youssef M. A.; Silva, Walter J.
The United States Geological Survey national seismic hazard maps have historically been produced for a reference site condition of VS 30 = 760 m/s. For other site conditions, site factors are used, which heretofore have been developed using ground motion data and simulations for shallow earthquakes in active tectonic regions. Research results from the Next Generation Attenuation–East (NGA-East) project, as well as previous and contemporaneous related research, demonstrate different levels of site amplification in central and eastern North America (CENA) as compared to active regions. We provide recommendations for modeling of ergodic site amplification in CENA based primarily on research results from the literature. The recommended model has three additive terms in natural logarithmic units. Two describe linear site amplification: an empirically constrained VS 30 -scaling term relative to a 760 m/s reference and a simulation-based term to adjust site amplification from the 760 m/s reference to the CENA reference of VS = 3000 m/s. The third term is a nonlinear model that is described in a companion document. All median model components are accompanied by epistemic uncertainty models.